2022
DOI: 10.1093/geront/gnac030
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in Older Adults’ Social Connections Throughout the Initial Year of the COVID-19 Pandemic

Abstract: Background and Objectives The COVID-19 pandemic exposed older adults to increased health risks, yet social distancing precautions also heightened risks to their social well-being. This mixed-methods study explores changes in older adults’ satisfaction with social engagement and interpersonal connections throughout the first year of the COVID-19 pandemic. Research Design and Methods A Midwestern sample of 76 older adults aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Older adults’ repeated emphasis on connection throughout the pandemic suggests they understood the benefit of social connection during and following the pandemic—for themselves and for their community. This emphasis may have resulted from increased isolation which highlighted the need for and benefit of social connections ( Fuller et al, 2022 ). Further, it is interesting to note that due to the unique geographic location of this sample, they may be well versed in navigating patterns of isolation and reconnection due to harsh winters which make local travel difficult ( Bjelde & Sanders, 2009 ; Hjorthol, 2013 ), especially among those in sparse or remote communities ( Scott, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Older adults’ repeated emphasis on connection throughout the pandemic suggests they understood the benefit of social connection during and following the pandemic—for themselves and for their community. This emphasis may have resulted from increased isolation which highlighted the need for and benefit of social connections ( Fuller et al, 2022 ). Further, it is interesting to note that due to the unique geographic location of this sample, they may be well versed in navigating patterns of isolation and reconnection due to harsh winters which make local travel difficult ( Bjelde & Sanders, 2009 ; Hjorthol, 2013 ), especially among those in sparse or remote communities ( Scott, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we hypothesized advice given a year into the pandemic would shift or differ from advice given early into the pandemic after having more time to reflect on previously proffered advice and enduring adversity (i.e., loss in autonomy, social connections, fear). For example, given older adults experienced increasing social isolation fatigue across the first year of the pandemic ( Fuller et al, 2022 ), they may have shifted from undervaluing social connections in their early advice to overemphasizing the importance of reestablishing social contact in later advice.…”
Section: Background and Objectivesmentioning
confidence: 99%
“…Many used video and social media to boost connectedness, while some engaged in digital volunteering and/or used the Internet to acquire new skills; however, these activities were sometimes mentally exhausting for this particular group. Perhaps most telling, Fuller et al (2022) interviewed 76 older adults aged 70-97 and found a notable difference in technology use dependent upon both age and attitude. Those in their 70s and early 80s were more willing to use video-technology to keep up with friends and family, but across all ages, there were some people who consistently reported reluctance to use digital means.…”
Section: Background Literature 21 Older Adults and The Digital Dividementioning
confidence: 99%
“…Others, however, were able to shop, socialize, or gain medical attention online. Clearly, there were major differences in the contexts in which older adults were asked to cope, with huge variation in both personal social networks, economic status, digital literacy, and attitude to technology use (e.g., Tabassum, 2020;Fuller et al, 2022), with those falling on the "wrong side of the senior digital divide" being much more likely to experience adverse effects of the pandemic (Robinson et al, 2020). In short, older adults showed great diversity in their ability to respond to digital upheaval, with some reporting positively about the transition to online activities as a means of coping (Rotenberg et al, 2021), while others doubled-down on their beliefs that technology solutions were not for them (Fuller et al, 2022).…”
Section: Background Literature 21 Older Adults and The Digital Dividementioning
confidence: 99%
“…Social support was shown to help individuals cope with the major stressors presented by the COVID‐19 pandemic (Webb & Chen, 2022), especially for older adults (Fuller & Huseth‐Zosel, 2021; Hadjistavropoulos & Asmundson, 2022). Social relationships, particularly family and friends, were utilized by older adults to support coping during the COVID‐19 pandemic (e.g., Fuller et al, 2023). However, not all older adults had family members readily available to meet this need—both because of the pandemic and situations predating the pandemic.…”
Section: Introductionmentioning
confidence: 99%